Digital interactive experience- and game-based fall interventions for community-dwelling healthy older adults: a cross-disciplinary systematic review - Celina Ciemer; Celina Ciemer; Lisa Kröper; Thomas Jürgen Klotzbier; Sabiha Ghellal; Nadja Schott (Frontiers in Public Health)
IntroductionFalls pose significant health risks to older adults, impacting their quality of life. Preventive strategies are crucial, as research shows that fall prevention interventions can effectively reduce fall risks. However, these interventions often suffer from low adherence and uptake. Digital, interactive interventions, incorporating experience-, and game-related aspects, offer a promising solution, making this topic inherently cross-disciplinary.ObjectiveThis review aims to assess the current landscape of digital interactive experience and game-based fall interventions for community-dwelling, healthy older adults. It focuses on integrating Human Movement Science and User Experience & Game Design perspectives, emphasizing the cross-disciplinary nature of this research.MethodsWe employed a cross-disciplinary literature search framework, searching the databases ACM-DL, IEEE-Xplore, ScienceDirect, PubMed, Scopus, and Web of Science. The review focused on healthy community-dwelling older adults (50+), including those at risk of falling. Excluded were studies involving chronic diseases, non-age-related impairments, other age groups, or individuals receiving care. Only digital, interactive fall prevention interventions without commercial software were considered. Studies published between 2000–2024 were included. A qualitative thematic synthesis was conducted, focusing on four categories: Objectives (O), Design and Development (D), Types of Intervention (T), and Evaluation Methods (E).ResultsThe search yielded 2,747 results, with 59 articles included in the final synthesis. Objectives were mainly driven by a combination of HMS and UXG rather than a single aspect. In Design and Development it was observed that concept-based design was scarce, with most being procedure-based. Descriptions of interventions frequently lacked specificity, particularly in-depth experience-related terminology and exercise descriptions. Evaluation methods were found to be more frequently informed by both HMS and UXG, although only four studies used a mixed-method approach to explore their interplay. Among included articles, most aspects incorporated both HMS and UXG across all four categories: O(n = 37), D(n = 37), T(n = 54), and E(n = 21).ConclusionThe review underscores the importance of digital interactive experience- and game-based fall prevention interventions. It highlights the need for enhanced cross-disciplinary collaboration between HMS and UXG to address gaps, such as the lack of a shared thesaurus and standardized guidelines, which are vital for improving transparency, reproducibility, and the refinement of these interventions.